2020
DOI: 10.3390/app10145001
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Nafion-Coated Stainless Steel Surfaces for Inhibiting Bacillus Subtilis Biofilm Formation

Abstract: Stainless steel is one of most commonly used materials in the world; however, biofilms on the surfaces of stainless steel cause many serious problems. In order to find effective methods of reducing bacterial adhesion to stainless steel, and to investigate the role of electrostatic effects during the formation of biofilms, this study used a stainless steel surface that was negatively charged by being coated with Nafion which was terminated by sulfonic groups. The results showed that the roughness of stainless s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Furthermore, the equilibration duration of TiN could be reduced by modifying the TiN layer with redox blocking membranes, which will broaden the application field of this sensor where fast response time is required. These modifications not only improve the sensors reaction time but also increase the proton exchange activity in the cell, adhesion, and overall performance [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the equilibration duration of TiN could be reduced by modifying the TiN layer with redox blocking membranes, which will broaden the application field of this sensor where fast response time is required. These modifications not only improve the sensors reaction time but also increase the proton exchange activity in the cell, adhesion, and overall performance [ 44 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, although the EPS-matrix represents the robust skeleton that protects the biofilm cells from stress, the eradication and detachment capacity of both DC and NPs were evident throughout the current study. This could be attributed to alterations in the physical-chemical characteristics of both biofilm and adherent surfaces (i.e., polymeric properties, hydrophobicity/hydrophilicity, charge, roughness, and surface free energies) induced by both treatments, which ultimately destabilized adhesion of the preformed biofilm to the surface [70,71]. Moreover, the involvement of water channels in the core structure of the biofilm, which allow mainly the transportation of nutrients, could permit the diffusion of toxic substances that generate ROS, which unambiguously cause cell damage [71][72][73].…”
Section: -9mentioning
confidence: 99%
“…This could be attributed to alterations in the physical-chemical characteristics of both biofilm and adherent surfaces (i.e., polymeric properties, hydrophobicity/hydrophilicity, charge, roughness, and surface free energies) induced by both treatments, which ultimately destabilized adhesion of the preformed biofilm to the surface [70,71]. Moreover, the involvement of water channels in the core structure of the biofilm, which allow mainly the transportation of nutrients, could permit the diffusion of toxic substances that generate ROS, which unambiguously cause cell damage [71][72][73]. This assumption was confirmed simultaneously via SEM (the presence of pores, pits, furrows, and cell deformation) and ROS results.…”
Section: -9mentioning
confidence: 99%
“…The electron flow will produce a direct electrical current, causing the potential differences between the anode and cathode compartments . The aromatic sulfonation (in Nafion) of a membrane may result in acidity changes in the anode, causing microbe inhibitions . The S. cerevisiae was used as a biocatalyst because of its resilience to environmental changes and its facile electron transfer mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…31 The aromatic sulfonation (in Nafion) of a membrane may result in acidity changes in the anode, causing microbe inhibitions. 32 The S. cerevisiae was used as a biocatalyst because of its resilience to environmental changes and its facile electron transfer mechanism. 33 Previously, it was shown that the S. cerevisiae, a eukaryote, was retrofitted into ethanol plants for in situ power generation; 34 in the short term, their configurations resulted in low device durability because of the poisoning of the biocatalyst.…”
Section: ■ Introductionmentioning
confidence: 99%